The Lbc Rho Guanine Nucleotide Exchange Factor/α-Catulin Axis Functions in Serotonin-induced Vascular Smooth Muscle Cell Mitogenesis and RhoA/ROCK Activation - Bear, Michael D. (American Society for Biochemistry and Molecular Biology, 2010)
Serotonin (5-hydroxytryptamine, 5-HT) is mitogenic for several cell types including pulmonary arterial smooth muscle cells (PASMC), and is associated with the abnormal vascular smooth muscle remodeling that occurs in pulmonary arterial hypertension. RhoA/Rho kinase (ROCK) function is required for 5-HT-induced PASMC mitogenesis, and 5-HT activates RhoA; however, the signaling steps are poorly defined. Rho guanine nucleotide exchange factors (Rho GEFs) transduce extracellular signals to Rho, and we found that 5-HT treatment of PASMC led to increased membrane-associated Lbc Rho GEF, suggesting modulation by 5-HT. Lbc knockdown by siRNA attenuated 5-HT-induced thymidine uptake in PASMC, indicating a role in PASMC mitogenesis. 5-HT triggered Rho-dependent serum response factor-mediated reporter activation in PASMC, and this was reduced by Lbc depletion. Lbc knockdown reduced 5-HT-induced RhoA/ROCK activation, but not p42/44 ERK MAP kinase activation, suggesting that Lbc is an intermediary between 5-HT and RhoA/ROCK, but not ERK. 5-HT stimulation of PASMC led to increased association between Lbc, RhoA, and the α-catulin scaffold. Furthermore, α-catulin knockdown attenuated 5-HT-induced PASMC thymidine uptake. 5-HT-induced PASMC mitogenesis was reduced by dominant-negative G(q) protein, suggesting cooperation with Lbc/α-catulin. These results for the first time define a Rho GEF involved in vascular smooth muscle cell growth and serotonin signaling, and suggest that Lbc Rho GEF family members play distinct roles. Thus, the Lbc/α-catulin axis participates in 5-HT-induced PASMC mitogenesis and RhoA/ROCK signaling, and may be an interventional target in diseases involving vascular smooth muscle remodeling.